Reduction in Medication Refill Encounters Through Primary Care Redesign Workflow Changes. Issue 1 (21st January 2022) - Swedlund, Matthew; Kamnetz, Sandra; Birstler, Jen; Trowbridge, Elizabeth; Arndt, Brian; Micek, Mark; Lochner, Jennifer; Pandhi, Nancy
Abstract : With a goal of improving efficiency and reducing workload outside of visits, we sought to examine a primary care redesign process aimed at reducing refill requests made outside of office visits. Data on the number of refill encounters per panel member were collected at 17 clinics before, during, and after the implementation of a redesign process. There was an initial reduction in the number of medication refill encounters, and the rate of refill encounters continued to decline following implementation. Variation across clinic contexts suggests that redesign processes may need to be tailored for different settings to optimize effectiveness.